Economic Efficiency in Indian Rubber Industry - Sarba Priya Ray (Contemporary Economics)
The article tries to assess the utilization efficiency of capacity of Indian rubber industry in terms of econometric framework for the period,1979-80 to 2008-09.Capacity output has been  obtained at the minimum point of short run average cost curve. The result suggests that there has been declining growth rate of capacity utilization in rubber industry of India during the post reforms period accompanied by declining output growth as well as capacity growth. There exists some excess capacity in the rubber industry which remains unutilized during our study period. The result exhibits that  high correlation coefficient between actual output and capacity output for Indian rubber sector implies that  major part of under utilization of capacity is intended and low correlation  between capacity expansion (CE) and past utilization(CUL) seems to suggest that under utilization, if any, is mainly of the unintended nature, capacity expansions do not  move in line with past utilization rates and it also indicates that abolition of restrictions on licensing due to trade liberalization do not  help industry to expand capacity. On the other hand, low correlation between capacity expansion (CE) and lagged output (QL ) indicates that unintended excess capacity is varying from year to year in an unsystematic matter.